3D printing of edible hydrogels containing thiamine and their comparison to cast gels. (July 2021) - Kamlow, Michael-Alex; Vadodaria, Saumil; Gholamipour-Shirazi, Azarmidokht; Spyropoulos, Fotis; Mills, Tom
Abstract: In this study, 3% w/v kappa-carrageenan (кC) and 2% w/v agar were assessed for their suitability for hot extrusion 3D printing (3DP) and compared to cast gels of equivalent composition. Moreover, incorporation of a model active (thiamine) at varying concentrations, was studied for both 3DP and cast microstructures. Rheology and differential scanning calorimetry showed that thiamine (via electrostatic complexation) reinforced the kappa-carrageenan gel network (up to a certain threshold concentration), whereas the agar gel was structurally unaltered by the active's presence. While the кC-thiamine formulations were printable (within a relatively narrow formulation/processing window), the agar-thiamine systems were not printable via the current set up. Texture profile analysis (TPA) showed that 3DP кC-thiamine cylinders had a hardness value of 860 g ± 11% compared to 1650 g ± 6% for cast cylinders. When compressed they delaminated due to failure between consecutive layers of material deposited during the printing process; light microscopy revealed distinct layering across the printed gel structure. Release tests at 20 °C showed printed gels expelled 64% ± 2.2% of the total active compared to 59% ± 0.8% from the cast gels over 6 h. At 37 °C these values increased to 78% ± 2.6% and 66% ± 3.5% respectively. This difference was believed to be due to the significant swelling exhibited by the printed systems. A simple empirical model, applied to the release data, revealed that thiamine discharge from 3DP gels was solely driven by diffusion while ejection of the active from cast systems had both diffusional and relaxation contributions. Graphical abstract: Image 1 Highlights: 3% w/v к-carrageenan and 2% w/v agar were assessed for hot extrusion 3D printing. Rheology and DSC showed thiamine electrostatically complexes with к-carrageenan. 3% w/v к-carrageenan gels containing 2% w/v thiamine were printable. Texture analysis showed printed gels are weaker and less elastic than cast gels. 3D printed hydrogels release thiamine at a faster rate than cast gels.